Sastra Digital: Antara Inovasi Bentuk dan Kebuntuan Metodologis - Mohammad Rokib; Lutfiyah Alindah; Parmin Parmin; Ririe Rengganis (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study examines the development of Indonesian digital literature through the identification of its forms and the accompanying methodological implications. Although literary production in the digital space is increasingly abundant and has received academic attention, there is still little attention examining the diversity of forms and its methodological consequences that arise from differences in material and medium. Two main problems that guide this study are how have Indonesian digital literary forms developed as a medium of expression, and what methodological challenges arise in examining them. This study then uses a historical-material approach borrowing Bolter and Grusin's media remediation framework. This study identifies four main categories: Material Digital Literature, Web-based Literature, App-based Literature, and Chat Literature as well as Generative Literature. Each form demonstrates transformations in the production and reception of literary texts, which require different methodological approaches. This article’s argument emphasizes the importance of alignment between method, medium form, and interpretive validity in the study of digital literature. These findings encourage the development of an adaptive approach in the study of Indonesian digital literature to achieve a sharp understanding of technological and authorial aspects.